2010
DOI: 10.1177/1363459310389626
|View full text |Cite
|
Sign up to set email alerts
|

Repertoires of ADHD in UK newspaper media

Abstract: This article applies discourse analysis to examine how Attention Deficit Hyperactivity Disorder has been represented and debated in UK newspapers in the last decade. Two repertoires of ADHD are identified as the biological and the psychosocial. The analysis shows how subjectivities are embedded in these repertoires, such that constructions of the problem child, abnormal or ordinary naughty child and ineffectual, neglectful, or confused parents support alternative versions of ADHD.The biological repertoire just… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
44
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 41 publications
(53 reference statements)
5
44
0
3
Order By: Relevance
“…Horton-Salway (2011) examined how UK newspapers have represented ADHD and identified two repertoires: the biological and the psychosocial. The biological repertoire describes ADHD as a neurological pathology and encourages its medication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horton-Salway (2011) examined how UK newspapers have represented ADHD and identified two repertoires: the biological and the psychosocial. The biological repertoire describes ADHD as a neurological pathology and encourages its medication.…”
Section: Introductionmentioning
confidence: 99%
“…The psychosocial repertoire put forward inadequate parenting practices and social problems such as poor school systems, excessive TV exposure or high level of premature birth. Horton-Solway (2011) observed that the psychosocial repertoire was dominant in UK newspapers during 2000–2009. However, Schmitz, Filippone, and Edelman (2003) identified the biological model of ADHD as dominant in US newspapers during 1988–1997 (Schmitz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, ADHD is a topic often covered in the newsprint media (Gonon, Konsman, Cohen, & Boraud, 2012; Horton-Salway, 2011). As Horton-Salway (2011) describe in one of the few studies of this topic, ADHD has become increasingly common in UK newsprint media reports of child behaviour.…”
mentioning
confidence: 99%
“…As Horton-Salway (2011) describe in one of the few studies of this topic, ADHD has become increasingly common in UK newsprint media reports of child behaviour. This author points to ontological distinctions in UK newsprint media representations between the biological and the psychosocial (Horton-Salway, 2011, p. 36).…”
mentioning
confidence: 99%
See 1 more Smart Citation